The nuclear pore complex: understanding its function through structural insight - Beck, Martin; Hurt, Ed (Nature reviews, 2017)
Nuclear pore complexes (NPCs) fuse the inner and outer nuclear membranes to form channels across the nuclear envelope. They are large macromolecular assemblies with a complex composition and diverse functions. Apart from facilitating nucleocytoplasmic transport, NPCs are involved in chromatin organization, the regulation of gene expression and DNA repair. Understanding the molecular mechanisms underlying these functions has been hampered by a lack of structural knowledge about the NPC. The recent convergence of crystallographic and biochemical in vitro analysis of nucleoporins (NUPs), the components of the NPC, with cryo-electron microscopic imaging of the entire NPC in situ has provided first pseudo-atomic view of its central core and revealed that an unexpected network of short linear motifs is an important spatial organization principle. These breakthroughs have transformed the way we understand NPC structure, and they provide an important base for functional investigations, including the elucidation of the molecular mechanisms underlying clinically manifested mutations of the nucleocytoplasmic transport system.